Residual characteristics and potential health risk assessment of polychlorinated biphenyls (PCBs) in seafood and surface sediments from Xiangshan Bay, China (2011–2016). (15th October 2020) - Lin, Shu; Zhao, Binfeng; Ying, Zeteng; Fan, Shiming; Hu, Zongqi; Xue, Feng; Zhang, Quan
Graphical abstract: Highlights: The residue and spatial distribution of PCBs in seafood were investigated. The biota-sediment accumulation factors were determined. Penta-CB and Hexa-CB was the dominant congeners in seafood. Abstract: Xiangshan Bay provides most of the seafood for residents from the southeast coast of China. However, information on the safety of local seafood was not well known. In this study, we investigated the residue, spatial distribution and potential health risks of ten polychlorinated biphenyls (PCBs) in seafood and surface sediment samples during six years (2011–2016). The results indicated the level of PCBs in 9 types of seafood from Xiangshan Bay ranged between ND and 25.3 ng·g −1 . The highest average concentration of PCBs (14.2 ng·g −1 ) was observed in Ostreidae . The average PCB concentrations in the surface sediments was 1.58 ng·g −1 (ND to 15.2 ng·g −1 ). The biota-sediment accumulation factors of the PCBs in most seafood indicated that the seafood was readily subjected to the bioaccumulation of PCBs from sediments. The carcinogenic risks were all within the safe ranges of 9 types of seafood for adults.